IMPROVING STUDENTS’ NARRATIVE WRITING ACHIEVEMENT BY USING STORYTELLING - Hamdy Hasmin; Amrin Saragih (Universitas Negeri Medan, 2013)
This research attempts to improve students’ achievement in writing narrative by using torytelling Technique. The result showed the improvement of students’ achievement in writing hortatory exposition text. It was found that the mean of the students’ scores in every test was improved. In the first test, the mean was 36.13 and there was 10% of the students who got up 75 points (Minimum Completeness Criteria), in the second test, it was 75.45 and 63.33% of the students who got up 75 points, and in the last one, the mean was 82.53 and there was 90% of the students who got up 75 points.The students felt enthusiastic, enjoyable, and active in teaching learning process by using storytelling Technique.The result of the research showed the progress of achievement scores, it can be concluded that storytelling gives contribution to improve students’ achievement in writing narrative.